A hybrid solar photovoltaic-wind turbine-Rankine cycle for electricity generation in Turkish Republic of Northern Cyprus. Issue 1 (31st December 2016) - Asumadu-Sarkodie, Samuel; Sevinç, Ҫağlan; Jayaweera, Herath M.P.C.
Abstract: This paper presents an energy demand model by designing a hybrid solar-wind-thermal power generation system of the Turkish Republic of Northern Cyprus, a promising substitute for the expensive battery banks. The study models the future energy demand of Turkish Republic of Northern Cyprus based on the IPCC emissions scenario A1B and A2 by designing a new hybrid solar-wind-thermal power system that satisfies the current and future requirements of firm capacity during peak periods. The study suggests an improvement in a hybrid solar-wind-thermal power system performance by predicting reliable outputs that can integrate renewable energy technologies to conventional power generation. The energy consumption prediction model emphasizes the energy requirement that has a growing demand from 300 to 400 GWh in scenario A1B and 150–450 GWh in scenario A2 from 2010 to 2050. The proposed design can meet 400 GWh of electricity demand in TRNC based on IPCC scenario A1B and 450 GWh of electricity demand in TRNC based on IPCC scenario A2. The percentage contribution of solar, wind and thermal energy for 2010, 2020, 2030, 2040 and 2050 are presented along with CO2 emissions and water consumption for each of the years.